PHILOSOPICAL OF SYAIKHONA KHOLIL’S MOSQUE IN DEVELOPING CHARACTER MADURESE LOCAL WISDOM - Syifauddin, Moh. (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2024)
The aim of this research is to explain the philosophical meaning of Syaikhona Kholil’s mosque in building the character and ethics of local Madurese wisdom using semiotic studies. This research focuses on the philosophical meaning of Syaikhona Kholil’s mosque in building character and ethics of Madurese local wisdom uses using semiotic studies using qualitative research methods, which are used to analyze meaning using systematic linguistic research. The data sources in this research were obtained from the results of a field survey and through interviews with the grave guard or caretaker of the Syaikhona Kholil Bangkalan mosque. Furthermore, the results of various interviews and surveys will then be analyzed using semiotic studies. From the results of this analysis, the philosophical meaning that appears and is contained in the mosque of Syaikhona Kholil Bangkalan can be classified. Then we can map the meaning contained in the mosque of Syaikhona Kholil. From the results of this analysis and mapping, religious tourism in Madura, especially Bangkalan, will be more widely introduced.